Enhanced hippocampal neurogenesis mediated by PGC-1α-activated OXPHOS after neonatal low-dose Propofol exposure - Chen, Keyu; Lu, Dihan; Yang, Xiaoyu; Zhou, Rui; Lan, Liangtian; Wu, Yan; Wang, Chen; Xu, Xuanxian; Jiang, Mei Hua; Wei, Ming; Feng, Xia (Frontiers in Aging Neuroscience, 2022)
Background: Developing brain is highly plastic which can be easily affected. Growing pediatric usage of anesthetics during painless procedures has raised concerns about the effect of low-dose anesthetics on neurodevelopment. It is urgently to ascertain the neuronal effect of low-dose Propofol, a widely used anesthetic in pediatrics, on developing brains. Methods: The behavioral tests after neonatal exposure to low-dose / high-dose Propofol in mice was conducted to clarify the cognitive effect. The nascent cells undergoing proliferation and differentiation stage in hippocampus and cultured neural stem cells (NSCs) were further identified. In addition, single-nuclei RNA sequencing (snRNA-seq), NSCs bulk RNA-seq, metabolism trials were performed for pathway investigation. Furthermore, small interfering RNA and stereotactic adenovirus injection were respectively used in NSCs and hippocampal to confirm the underlying mechanism. Results: Behavioral tests in mice showed enhanced spatial cognitive ability after exposed to low-dose Propofol. Activated neurogenesis was observed both in hippocampal and cultured NSCs. Moreover, transcriptome analysis of snRNA-seq, bulk RNA-seq and metabolism trials revealed a significant enhanced oxidative phosphorylation (OXPHOS) level in NSCs. Furthermore, PGC-1α, a master regulator in mitochondria metabolism, was found upregulated after Propofol exposure both in vivo and in vitro. Importantly, down-regulation of PGC-1α remarkably prevented the effects of low-dose Propofol in activating OXPHOS and neurogenesis. Conclusions: Taken together, this study demonstrates a novel alteration of mitochondrial function in hippocampal neurogenesis after low-dose Propofol exposure, suggesting the safety, even potentially beneficial effect, of low-dose Propofol in pediatric use.